Revolutionizing Dining Experience: Building Restaurant Reservation Application - Yohanes Dwi Raharjo; Octaviyanti Dwi Wahyurini (Dinasti International Journal of Education Management And Social Science, 2024)
The development of digital technology has transformed business models and created new value for customers and restaurant owners. One of the challenges faced in the restaurant industry is related to queues and reservations. This research aims to investigate business design strategies that can be used by startups in the restaurant industry. In this study, two main approaches are used: lean startup and service design. Qualitative methods in the form of interviews and testing were conducted on restaurant managers and visitors in the city of Kediri with respondents from the millennial and Generation Z demographics. During the data collection phase, a comparison of existing reservation applications was carried out. It was found that reservation services are limited to large cities, presenting an opportunity and business potential for new startups. Interviews were also conducted to validate the queue problem experienced by both restaurant visitors and managers. The results showed that 91% of respondents stated that the queue problem is valid and important to resolve. Based on this data, the author attempts to outline a new startup business idea and reservation application as a solution using a lean canvas. The lean startup approach used in this research focuses on accelerating the creation of a minimum viable product (MVP) in the form of the reservation application Eat-Eat. The service design approach, through a service blueprint, was used to observe the business processes and interactions of the related stakeholders. The combination of these two methods complements each other and makes the offered MVP more aligned with customer needs and preferences. A mockup prototype of the Eat-Eat reservation application was created using Figma software and tested on 11 respondents to assess its usability. Using the system usability scale (SUS) method, an average final score of 88 was obtained, compared to the standard average SUS score of 68 set by Jeff Sauro. This means that the Eat-Eat reservation application prototype is acceptable and feasible to use. During interviews and testing, the author received a lot of positive feedback for the development and improvement of the application. In the final stage, the prototype, which has been refined through an iterative process and deemed feasible, will become the final application ready for launch. It is hoped that the results of this research will provide valuable insights for startup founders and co-founders to develop more effective business design strategies, creating more innovative, relevant, and sustainable products and services.